Maternal prenatal stress and its effects on primary pregnancy outcomes in twin pregnancies - Wenling Wang; Li Wen; Yan Zhang; Lan Wang; Longqiong Wang; Zhi Chen; Lan Zhang; Chen Zhang; Jie Li; Chao Tong; Hongbo Qi; Richard Saffery; et al. (Taylor & Francis Group, 2020)
Objective: To assess the prevalence and degrees of maternal prenatal stress among twin-pregnant women and to investigate the impact of prenatal stress on primary pregnancy outcomes. Methods: The Chongqing Longitudinal Twin Study (LoTiS) began in December 2015 in China. Participants of LoTiS who met the inclusion criteria were recruited into this study and completed a stress rating scale (PSRS) in both early and late pregnancy. Maternal prenatal stress was examined in subgroups. Correlations between maternal prenatal stress and primary pregnancy outcomes were analyzed by multivariate logistic regression. Results: A total of 215 eligible twin pregnancies from LoTiS were recruited into this study. The overall mean scores of prenatal stress were 43.41 ± 19.84 and 51.33 ± 20.43 in early and late pregnancy, respectively. The first prenatal stressor was regarding concern about the pregnancy and childbirth safety. Subgroup analyses revealed prenatal stress in late pregnancy that differed based on different pregravid BMIs and education levels. Correlation analysis suggested that the risk of preterm premature rupture of membranes increases 1.8% per unit of stress scale in late pregnancy (OR = 1.018, 95% CI 1.001-1.025). Conclusions: Prenatal stress in twin pregnancies increases with the progression of pregnancy. Higher stress in late pregnancy is associated with a higher risk of premature rupture of membranes; therefore, interventions might be essential for improving pregnancy outcomes.